“It takes time to see the whole picture”: patients’ views on improvement in cognitive behavioral therapy and psychodynamic therapy after three years - Malkomsen, Anders; Røssberg, Jan Ivar; Dammen, Toril; Wilberg, Theresa; Løvgren, André; Ulberg, Randi; Evensen, Julie (Frontiers in Psychiatry, 2024)
There is a lack of qualitative research that retrospectively explores how patients with major depressive disorder view their improvement in psychotherapy. Fifteen patients who received shortterm cognitive behavioral therapy and psychodynamic therapy were individually interviewed approximately three years after completing therapy. Some patients had altered their views on therapy, especially those who initially were uncertain of how helpful therapy had been. They said they did not realize the extent and importance of their improvement in therapy before some time had passed, which can be explained by the surprising cumulative effects of seemingly small changes. This should make retrospective qualitative research an important part of future psychotherapy research.